E3 ubiquitin ligase SYVN1 as a promising therapeutic target for diverse human diseases - Li Zhu; Yong-Ping Liu; Yuan-Wang; Bo-Xuan Sun; Yu-Ting Huang; Ji-Kai Zhao; Jian-Feng Liu; Li-Ming Yu; Hui-Shan Wang (Pharmacological Research)
Numerous studies conducted in recent years indicate that mammalian E3 ubiquitin ligases serve as key regulators in the maintenance of cellular homeostasis by targeting the ubiquitination of substrate proteins and activating downstream signaling pathways. SYVN1, an E3 ubiquitin ligase, is characterized by its significant functions in regulating various biological processes, including molecular mechanisms related to gene expression, signaling pathways, and cell death, among others. Consequently, SYVN1 plays a crucial role in both normal human physiology and the pathogenesis of various diseases, such as oncogenesis, cardiovascular disorders, immune regulation, skeletal anomalies, and neurological diseases. This review synthesizes recent findings regarding the physiological and pathophysiological roles of SYVN1, offering new insights into potential strategies for the prevention and treatment of human diseases, as well as suggesting avenues for future drug development. In this Review, we summarize the latest findings regarding the physiological and pathophysiological roles of SYVN1, elucidating the mechanisms by which SYVN1 can regulate the progression of various diseases in humans. These important findings provide new avenues for further investigation of SYVN1 protein, new insights into potential strategies to prevent and treat human diseases, and new directions for future drug development.